Interaction between housing prices and household borrowing in Finland - Elias Oikarinen (The Research Institute of the Finnish Economy (ETLA), 2008)
Housing prices and household borrowing are expected to be tightly connected to each other. Better availability of credit eases liquidity constraints of households, which is likely to lead to higher demand for housing. On the other hand, housing prices may significantly influence household borrowing through various wealth effects. Employing time series econometrics this study shows that since the financial liberalization in the late 1980s there has been a significant two-way interaction between housing prices and housing loan stock in Finland. Before the financial deregulation the interaction was substantially weaker. Furthermore, housing appreciation has a notable positive impact on the amount of consumption loans withdrawn by households. It appears that there is no similar relationship between stock price movements and household borrowing. Understanding the two-way interaction between housing prices and credit is of importance, since the interdependence is likely to augment boom-bust cycles in the economy and increase the fragility of the financial sector.
Keywords: E41; E51; R21; 330; lending; borrowing; housing; stocks; dynamics; Unternehmensentwicklung; Immobilienpreis; Vermögen; Privater Haushalt; Haushaltsökonomik; Kredit; Verbraucherkredit; Finnland